Prospective Analysis Between Neutrophil-to-Lymphocyte Ratio on Admission and Development of Delirium Among Older Hospitalized Patients With COVID-19 - Fernández-Jiménez, Eduardo; Muñoz-Sanjose, Ainoa; Mediavilla, Roberto; Martínez-Alés, Gonzalo; Louzao, Iker I.; Andreo, Jorge; Cebolla, Susana; Bravo-Ortiz, María-Fe; Bayón, Carmen (Frontiers in Aging Neuroscience, 2021)
Objective: To examine any prospective association between neutrophil-to-lymphocyte ratio (NLR) at hospital admission and subsequent delirium in older COVID-19 hospitalized patients comparing by sex and age groups. Methods: The sample consisted of 1,785 COVID-19 adult inpatients (minimum sample size required of 635 participants) admitted to a public general hospital in Madrid (Spain) between March 16th and April 15th, 2020. Variables were obtained from electronic health records. Binary logistic regression models were performed between baseline NLR and delirium adjusting for age, sex, medical comorbidity, current illness severity, serious mental illness history and use of chloroquine and dexamethasone. An NLR cut-off was identified, and stratified analyses were performed by age and sex. Also, another biomarker was tested as an exposure (the systemic immune-inflammation index –SII). Results: 55.3% of the patients were men, with a mean age of 66.8 years. Roughly 13% of the patients had delirium during hospitalization. NLR on admission predicted subsequent delirium development (adjusted OR =1.02, 95 percent CI: 1.00–1.04, p = 0.024). Patients between 69-80 years with NLR values > 6.3 presented a two-fold increased risk for delirium (p = 0.004). There were no sex differences in the association between baseline NLR and delirium (p > 0.05) nor SII predicted delirium development (p = 0.341). Conclusions: NLR is a good predictor of delirium during hospitalization, especially among older adults, independently of medical comorbidity, illness severity and other covariates. Routine blood tests on admission might provide valuable information to guide the decision-making process with these especially vulnerable patients.